Magnetic field sensor with optical fiber bitaper-based interferometer coated by magnetic fluid - Zheng, Yangzi (2015)
An optical fiber magnetic field sensor is demonstrated using a waist-enlarged fusion bitaper-based optical fiber Mach-Zehnder interferometer (MZI) coated by magnetic fluid (MF). Since refractive index (RI) of the MF is sensitive to magnetic field, differential effective RI of the sensing fiber and hence transmission spectrum of the MZI are modulated. In addition, structural pattern state of the nanoscaled magnetic particles in the MF changes with magnetic field strength, leading to variation in contrast of the interference pattern through scattering-induced loss of the cladding modes, which interfere with the core mode. By monitoring wavelength shift or intensity change of a transmission dip of the MF-coated MZI, magnetic field strength measurement is realized with sensitivity up to -24 pm/Oe or 0.085 dB/Oe for wavelength and intensity measurements, respectively.